Rare Animals of India. - Singaravelan, Natarajan (Rare Animals of India., 2013)
Rare Animals of India is a unique book that presents the biological and ecological accounts of the least known animal species of India in one comprehensive volume. The book gives comprehensive ecological accounts supported with data tables on rare and specific animal species of India and discusses the basis for their rarity and their conservation. It includes information about the Indian Gharial (Gavialis gangeticus) the endangered Forest Owlet (Heteroglaux blewitti), the Bengal Marsh Mongoose, Snow Leopards and many more. Readers are guided through several chapters each detailing a specific k.